Elderly Onset Primary Intestinal Lymphangiectasia—A Rare Case - Li‐Han Goh; Madhavan Manoharan; Khean‐Lee Goh (JGH Open)
ABSTRACT Primary intestinal lymphangiectasia (PIL) is a rare protein‐losing gastroenteropathy characterized by diffuse or localized ectasia of the enteric lymphatics, which can be accompanied by lymphatic abnormalities in other parts of the body. This condition results in hypoalbuminemia, hypogammaglobulinemia, and lymphopenia due to the abnormal leakage of lymphatic fluid into the gastrointestinal tract. As there are no specific serological or radiological tests available, the gold standard for diagnosing intestinal lymphangiectasia is endoscopic examination with histopathological examination of intestinal biopsy specimens. We present a rare case of primary intestinal lymphangiectasia in a 62‐year‐old Chinese woman who presented with a six‐month history of lethargy, persistent diarrhea, and progressive weight loss. Gastroscopy and colonoscopy were performed, and biopsies revealed dilated intestinal lymphatics with broadened villi in the small intestine. Secondary causes of intestinal lymphangiectasia were ruled out, confirming the diagnosis of PIL. The patient was treated with a high‐protein, low‐fat diet supplemented with medium‐chain triglycerides, resulting in significant clinical improvement.